Innovations and Applications in Lightweight Concrete: Review of Current Practices and Future Directions - Diptikar Behera; Kuang-Yen Liu; Firmansyah Rachman; Aman Mola Worku (Buildings, 2025)
Lightweight concrete (LWC) has emerged as a transformative material in sustainable and high-performance construction, driven by innovations in engineered lightweight aggregates, supplementary cementitious materials (SCMs), fiber reinforcements, and geopolymer binders. These advancements have enabled LWC to achieve compressive strengths surpassing 100 MPa while reducing density by up to 30% compared to conventional concrete. Fiber incorporation enhances flexural strength and fracture toughness by 20–40%, concurrently mitigating brittleness and improving ductility. The synergistic interaction between SCMs and lightweight aggregates optimizes matrix densification and interfacial transition zones, curtailing shrinkage and bolstering durability against chemical and environmental aggressors. Integration of recycled and bio-based aggregates substantially diminishes the embodied carbon footprint by approximately 40%—aligning LWC with circular economy principles. Nanomaterials such as nano-silica and carbon nanotubes augment early-age strength development by 25% and refine microstructural integrity. Thermal performance is markedly enhanced through advanced lightweight fillers, including expanded polystyrene and aerogels, achieving up to a 50% reduction in thermal conductivity, thereby facilitating energy-efficient building envelopes. Although challenges persist in cost and workability, the convergence of hybrid fiber systems, optimized mix designs, and sophisticated multi-scale modeling is expanding the applicability of LWC across demanding structural, marine, and prefabricated contexts. In essence, LWC’s holistic development embodies a paradigm shift toward resilient, low-carbon infrastructure, cementing its role as a pivotal material in the evolution of next-generation sustainable construction.